دراسة ومقارنة أنظمة كشف الاختراقات المفتوحة المصدر - ديوب بشرى (Latakia University Journal -Engineering Sciences Series, 2016)
ظهرت أنظمة كشف الاختراقات Intrusion Detection Systems IDS، من أجل زيادة وتطوير الأمن في الشبكات، وأصبحت فعالة لحماية الشبكات الداخلية internal networks من الهجمات الخارجية، واتخاذ الإجراءات المناسبة ضد المخترقين intruders. كما تستخدم أنظمة كشف الاختراق تقنيات من أجل جمع معلومات عن الهجوم، ومن الممكن استخدام هذه المعلومات كدليل ضد المهاجم. تستخدم أنظمة كشف الاختراقات طرائق مختلفة في عملية الكشف، فبعضها يستخدم التواقيع في الكشف signature based، وبعضها يكشف الشذوذ anomaly based، وغيرها من الطرائق. يقارن هذا البحث التقنيات المستخدمة في أنظمة كشف الاختراق، ويركز على الأنظمة التي تستخدم التواقيع في عملية الكشف، وبالأخص النظامين snort وBro، وهما من الأنظمة المفتوحة المصدر open source، ومقارنة الإنذارات التي يطلقها النظامان عند تطبيق أداة توليد الهجمات IDSWakeup. With the recent advances in the field of network security, a technique called Intrusion Detection System IDS is developed to further enhance and make network secure. It is a way by which we can protect our internal network from outside attack, and can take appropriate action if needed. Using intrusion detection methods, information can be collected from known types of attack and can be used to detect if someone is trying to attack the network. Many techniques are there to detect intrusion in a network like signature matching, anomaly based and others. The work presented here studies and compares the techniques used by intrusion detection systems, and focuses on the signature matching technique. It discusses the open source, free intrusion detection system Snort. Another open source intrusion detection system Bro is also discussed. It compares these systems alarms against the open source tool IDSWakeup.